2020
DOI: 10.1016/j.neuroimage.2020.117180
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities of connectomic neuromodulation

Abstract: The process of altering neural activity – neuromodulation – has long been used to treat patients with brain disorders and answer scientific questions. Deep brain stimulation in particular has provided clinical benefit to over 150,000 patients. However, our understanding of how neuromodulation impacts the brain is evolving. Instead of focusing on the local impact at the stimulation site itself, we are considering the remote impact on brainregions connected to the stimulation site. Brain connectivity information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
113
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 145 publications
(115 citation statements)
references
References 141 publications
(168 reference statements)
1
113
1
Order By: Relevance
“…The classification analysis confirms the potential clinical relevance of the neuromarkers of pandemic-related anxiety and also highlights the higher susceptibility to mental distress (e.g., pathological anxiety) during the pandemic. The anxiety-specific neuromarkers may provide a special contribution to novel clinical practice for stress and anxiety reduction, such as defining connectome-based targets for neuromodulation (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…The classification analysis confirms the potential clinical relevance of the neuromarkers of pandemic-related anxiety and also highlights the higher susceptibility to mental distress (e.g., pathological anxiety) during the pandemic. The anxiety-specific neuromarkers may provide a special contribution to novel clinical practice for stress and anxiety reduction, such as defining connectome-based targets for neuromodulation (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Applying normative connectome data to brain stimulation sites in 95 patients from two centers, the study concluded that effective STN-DBS electrodes would modulate a region within the STN that was functionally connected to large portions of the prefrontal cortex, including supplementary motor area (SMA) and inferior frontal cortex (IFC) and functionally anticorrelated with primary motor cortex (M1). Similar studies accumulated evidence that neuromodulation of a specific network may result in clinical responses specific to a certain symptom (for a review see Horn and Fox 6 ). Following this concept of circuitopathies – networks with impact on specific symptoms or behaviors – it might be possible to modulate the same network at different stimulation sites to reach similar changes in clinical or behavioral outcomes.…”
Section: Introductionmentioning
confidence: 66%
“…Augmenting such an analysis with additional cohorts could one day lead to a personalized DBS targeting the network tailored to the leading symptom in each patient. 6…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the complexity and specificity of neural pathways and circuits in the mammalian nervous system is a major goal for neuroanatomists and is vital to understand and treat nervous system injuries and disorders (Nassi et al, 2015;Zeng, 2018;Horn and Fox, 2020;Lanciego and Wouterlood, 2020;Ugolini, 2020;Wong et al, 2020). The development and refinement of technologies such as functional near-infrared spectroscopy (Cao et al, 2015;Hu et al, 2020), diffusion weighted magnetic resonance imaging (Jeurissen et al, 2019;Yeh et al, 2020), and resting-state functional magnetic resonance imaging (Fox and Raichle, 2007;Horn and Fox, 2020) have enhanced our understanding of macroscale connectomics, and improved patient treatments and outcomes (Horn et al, 2017;Joutsa et al, 2018;Okromelidze et al, 2020). Mesoscale connectomics-characterizing a single population of neurons and/or connectivity of those neurons-has made similar progress (Lanciego and Wouterlood, 2020;Ugolini, 2020), but traditional tracers such as horseradish peroxidase, cholera toxin subunit B (CTB), hydroxystilbamidine (known commercially as Fluoro-Gold), and conjugated dextran amines [which include biotinylated dextran amine (BDA), and rhodamine conjugated dextran amine (RDA), also known as Fluoro-Ruby (FR) or Mini Ruby depending on molecular weight] remain the most widely used technique.…”
Section: Introductionmentioning
confidence: 99%